Do fim ao recomeço: um estudo do conto "O vaso azul", de João Anzanello Carrascoza - Minas, Juliana Galvão Marques (2017)
This research is a study of the short story “O vaso azul”, written by contemporary Brazilian author João Anzanello Carrascoza. It is divided in three parts: a critical presentation of the author’s works; a comparison of the three existing versions of the short story, with reflections on the interventions made during the rewriting process; and finally an interpretation of the text, seeking to establish dialogues, both literary and interart.